Cholecystokinin Modulates the Mucosal Inflammatory Response and Prevents the Lipopolysaccharide-Induced Intestinal Epithelial Barrier Dysfunction. Issue 2 (February 2020) - Saia, Rafael Simone; Ribeiro, Aline Barbosa; Giusti, Humberto
Abstract : ABSTRACT: The intestinal mucosa plays a critical role in the organism, acting as an interface between the lamina propria and the harmful antigens in the lumen. Sepsis is associated with primary injury to the intestinal mucosa, which in turn induces bacterial translocation and hyperpermeability. Cholecystokinin (CCK) is a peptide synthesized by several cell types, whose immunomodulatory activity has been reported in experimental models of inflammation. We hypothesized that the CCK treatment could modulate the inflammatory response and protect the integrity of the intestinal barrier in endotoxemic rats. Ten minutes before the endotoxemia induction by lipopolysaccharide (LPS) administration, rats were pretreated with CCK at two doses (0.4 μg/kg or 40 μg/kg). Mucosal permeability, bacterial translocation, cytokines production, histology injury, and expression of tight junction (TJ) proteins were the parameters assessed. In the early phase of endotoxemia, rats exhibited impaired intestinal barrier function, increased mucosal permeability, bacterial translocation, and also hyperactivation of the inflammatory response. On the other hand, the pretreatment with CCK modulated the mucosal production of pro-inflammatory cytokines and increased the expression of seal-forming TJ proteins (occludin, claudin-1 and junctional adhesion molecule (JAM-A)) only in the colon and also, reduced the bacterial counts in the mesenteric lymph nodes. However, CCK has a site-specific mechanism of action in the colon via CCK-1R, which is upregulated by the CCK treatment. In synergy with previous findings from our research group, the present results demonstrated that CCK preserves the integrity of the intestinal mucosa and might be a promising hormonal adjuvant therapy for the treatment of sepsis. Abstract : Supplemental Digital Content is available in the text